Pengaruh Good Corporate Governance dan Loyalitas terhadap Keputusan Nasabah serta Dampaknya terhadap Kualitas Produk - Eka Rahayuningsih (Fakultas Ekonomi, UIN Maliki Malang, 2021)
The purpose of this study is to determine the Effect of Good Corporate Governance and Loyalty on Customer Decisions and Their Impacts on Product Quality. The method used is a quantitative type of associative hypothesis. The analysis used is path analysis. The results of this study will prove five hypotheses. The first hypothesis shows the effect of Good Corporate Governance on Decision has a significant effect with p value 0.05 of 0.000. The second hypothesis shows the effect of Loyalty on Decisions has a significant effect with p value 0.05 of 0.000. The third hypothesis shows the effect of Good Corporate Governance on Product Quality has a significant effect with p value of 0.05 of 0.016. The fourth hypothesis shows the effect of Loyalty on Product Quality has a significant effect with p value of 0.05 of 0.049. The fifth hypothesis shows the influence of Decision on Product Quality has a significant effect with p value 0.05 of 0,000. Path analysis I shows the effect of Good Corporate Governance through Loyalty to product quality directly by 0.044 and indirect effect of 0.293. Path analysis II shows the effect of through Decision on product quality directly at 0.080 and indirect effect at 0.347.